Învățarea prin rezolvarea de probleme (problem-based learning): aspecte privind româna ca limbă străină (Romanian Studies Today, 2024)
This paper discusses the significance of Problem-Based Learning (PBL) as an effective teaching and learning method in classes for Romanian as a foreign language. PBL promotes active learning by immersing students in real-life scenario simulations, allowing them to discover solutions independently, with the teacher acting as a facilitator. This approach has proven particularly beneficial in developing conversational skills, as students create dialogues based on topics relevant to practical situations. However, PBL has been underutilized in teaching grammar, where traditional methods predominantly involve direct instruction of rules. To address this gap, we advocate for the integration of PBL in grammar instruction. We propose a linguistic Olympiad problem model, wherein students receive a set of data from an unfamiliar language and must identify its grammatical rules through critical thinking, analogy, and deduction. This method not only enhances grammatical understanding but also fosters essential analytical skills among students.